(untitled) (Scientific journal of the Fergana State University, 2023)
This scientific article depicts the emergence of the concept of "Wahdat ul-Wujud" in the Sufi views of Abu Bakr Muhammad Ibn Arabi, the teachings that influenced the emergence of the concept of "Wahdat ul-Wujud" and the attitudes of medieval religious scholars in relation to this concept.